2022
DOI: 10.1039/d1cp04975e
|View full text |Cite
|
Sign up to set email alerts
|

High activity of step sites on Pd nanocatalysts in electrocatalytic dechlorination

Abstract: The role of step sites on nanocatalysts in electrocatalytic dechlorination reaction (ECDR) is studied by using 3 Pd nanocatalysts with different density of step sites, which is decreasing on tetrahexahedral...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Based on the results, Pd/C has the best catalytic impact on the degradation of WPVC through catalytic HTT; therefore, it was used in the remaining trials to study the effects of (1) catalyst loading ratio, (2) HTT temperature, and (3) residence time. Pd/C may exhibit high catalytic activity in dechlorination processes, potentially making it more efficient in promoting the cleavage of CCl bonds in PVC and leading to better dichlorination 40 . In addition, Pd/C may display better selectivity for desired dechlorination products, reducing unwanted byproducts 41 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results, Pd/C has the best catalytic impact on the degradation of WPVC through catalytic HTT; therefore, it was used in the remaining trials to study the effects of (1) catalyst loading ratio, (2) HTT temperature, and (3) residence time. Pd/C may exhibit high catalytic activity in dechlorination processes, potentially making it more efficient in promoting the cleavage of CCl bonds in PVC and leading to better dichlorination 40 . In addition, Pd/C may display better selectivity for desired dechlorination products, reducing unwanted byproducts 41 .…”
Section: Resultsmentioning
confidence: 99%
“…54 Pd catalyst may exhibit higher catalytic activity and selectivity towards dechlorination reactions, leading to more efficient conversion of WPVC into less chlorinated or chloro-organic compounds. 40 Moreover, the unique surface properties and electronic structure of Pd contribute to its enhanced performance, as they promote the adsorption and activation of chlorine-containing WPVC molecules, enabling efficient dechlorination reactions. 41 the Pd/C loading is increased from 2.5% to 5%.…”
Section: Catalytic Dechlorination Of Wpvcmentioning
confidence: 99%
See 1 more Smart Citation
“…This work provides a more in-depth insight into the mechanism of the EHDC reaction on Pd, which could facilitate the proper selection of suitable catalysts and operating conditions (Figure 9c−g). Lou et al 172 studied the role of step center on Pd nanoparticles in the electrocatalytic dechlorination process with tetrahedral Pd (310) and cubic Pd (100) nanoparticles as models and alachlor as model pollutants. The results showed that the tetrahedral Pd (310) nanoparticles with rich steps had a higher electrocatalytic performance than the cubic Pd (100) nanoparticles with terrace sites.…”
Section: Regulation Of D-bandmentioning
confidence: 99%
“…In this study, we provide an assessment on potential effect of catalysis efficiency of the interfacial organization of TCE, TCB, and PCB77 as chosen adsorbates on three different substrates, namely Pd {111}, Pd {110}, and Pd {100} at various liquid temperatures. The reaction mechanisms in our recent work (Shenoy et al, 2021) and others (Lou et al, 2022;Pavloudis et al, 2022) using density functional theory (DFT) have provided an insight into how facet-specific optimal adsorption leads to efficient dechlorination, where molecular orientation will affect dechlorination mechanism and thus affect the catalytic efficiency. To tackle such problems, a system including hundreds of containment molecules using DFT or ab initio MD methods is longed for, but way beyond the capability of simulations.…”
Section: Introductionmentioning
confidence: 99%